Genome DNA sequencing around the EF-1 alpha multigene locus of Arabidopsis thaliana indicates a high gene density and a shuffling of noncoding regions. - Tremousaygue, D; Bardet, C; Dabos, P; Regad, F; Pelese, F; Nazer, R; Gander, E; Lescure, B (Genome Research, 1997)
In Arabidopsis thaliana, EF-1 alpha proteins are encoded by a multigene family of four members. Three of them are clustered at the same locus, which was positioned 24 cM from the top of chromosome 1. A region of DNA spanning 63 kb around these locus was sequenced and analyzed. One main characteristic of the locus is the mosaic organization of both genes and intergenic regions. Fourteen genes were identified, among which only four were already described, and other unidentified are most likely present. Functionally diverse genes are found at close intervals. Exon and intron distribution is highly variable at this locus, one gene being split into at least 20 introns. Several duplications were found within the sequenced segment both in coding and noncoding regions, including two gene families. Moreover, a sequence corresponding to the 5' noncoding region of the EF-1 alpha genes and harboring a 5' intervening sequence is duplicated and found upstream of several genes, suggesting that noncoding regions can be shuffled during evolution.